Implementation of fixed assets audit at PT U by KAP Y - Amalia, Dianafi Rizka; Laksmi, Ayu Chairina (Proceeding International Conference on Accounting and Finance, 2024)
Fixed asset audits are an important part of a company’s audit process. The components that make up fixed assets are generally considered to have material value because they represent the majority of the company’s total asset value and have the potential to make a significant contribution to the total value stated in the financial statements. Public Accounting Firms (KAP) such as KAP Y play an important role in carrying out the fixed asset audit process. The purpose of the research entitled "Implementation of Fixed Asset Audit at PT U by KAP Y" is to describe the fixed asset audit procedures carried out. The research method used is a qualitative-descriptive method with data collection methods through observation, interviews, use of documents and literature. The data analysis method used is descriptive analysis technique. The research results show that the fixed asset audit procedures carried out by KAP Y consist of pre-engagement, planning, testing and reporting stages. The audit procedures carried out by KAP Y have been going well and are in accordance with the Standard Public Accountant Guidelines. The novelty of this research is that the research context focuses on KAP Y’s fixed asset audit procedures carried out at PT U using the latest regulations.